Hydroxyproline Excretion and Height Velocity in Adolescent Boys - Zorab, P. A. (1970)
The height velocity of 122 boys of 11 to 17 years is compared with their urinary total hydroxyproline excretion and a close relation is shown. The importance of this is discussed in relation to undersized children and to those with scoliosis in whom rapid growth is often associated with increasing curvature of the spine. Poor correlation was found between urinary total hydroxyproline excretion and height, weight, body surface area, and creatinine excretion.